Relaying strategies and protocol designs for buffer-aided cooperative relaying networks - Luo, Sheng (2017)
In this thesis, a new technique named buffer-aided relaying is studied to enhance the performance of wireless relaying networks. In particular, the transmission strategies that can improve diversity gain, maximize the system throughput and reduce the information delay are investigated.